Retention of activity by the new generation platinum agent AMD0473 in four human tumour cell lines possessing acquired resistance to oxaliplatin - Sharp, S.Y; O'Neill, C.F; Rogers, P; Boxall, F.E; Kelland, L.R (European journal of cancer (1990), 2002)
Four models of acquired resistance to the clinically-used platinum drug, oxaliplatin, have been established using human tumour cell lines in vitro; two colon (HCT116 and HT29) and two ovarian (A2780 and CH1). Levels of acquired resistance ranged from 3.0- to 15.8-fold with levels of resistance higher in the colon relative to the ovarian carcinoma cell lines. Notably, the platinum analogue, AMD0473, currently undergoing clinical evaluation, exhibited superior circumvention of acquired oxaliplatin resistance in comparison to either cisplatin or the trinuclear platinum BBR3464. Resistance in the two colon cell lines was unique to oxaliplatin itself among the platinum drugs studied. Acquired oxaliplatin resistance was not due to either reduced drug membrane transport or increased levels of glutathione in any of the four resistant lines. Following exposure to oxaliplatin, a lower level of platinum–DNA adducts was present in acquired oxaliplatin-resistant HT29 cells. In the remaining resistant lines, there was no change in the levels of platinum–DNA adducts relative to the parent lines. There was no change in hMLH1 DNA mismatch repair gene status in any of the four cell line pairs. However, in an A2780 subline where loss of hMLH1 and a p53phe172 mutation occurred, 5-fold resistance to cisplatin was observed, but only 1.7-fold resistance to oxaliplatin and no resistance to AMD0473 were observed. Re-introduction of hMLH1 into these cells caused no significant change in the sensitivity to cisplatin, oxaliplatin or AMD0473. These data show that acquired resistance to oxaliplatin may occur in cell lines (and therefore probably in the clinic) and in the four independent cell lines studied this was circumvented by AMD0473. Alongside previously described models of acquired resistance to cisplatin, these oxaliplatin-resistant cell line models may be useful in the evaluation of further novel platinum agents.